2021
DOI: 10.1159/000516681
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Imaging and Clinical Methods to Estimate Prostate Volume: A Single-Centre Retrospective Study

Abstract: <b><i>Background:</i></b> Prostate volume (PV) is a useful tool in risk stratification, diagnosis, and follow-up of numerous prostatic diseases including prostate cancer and benign prostatic hypertrophy. There is currently no accepted ideal PV measurement method. <b><i>Objective:</i></b> This study compares multiple means of PV estimation, including digital rectal examination (DRE), transrectal ultrasound (TRUS), and magnetic resonance imaging (MRI), and radical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 36 publications
3
28
0
Order By: Relevance
“…For the risk stratification of cancer, PSA density or PSA divided by prostate volume is a reliable biomarker. In a recent article, Massanova et al [20] reported that the actual surgical specimen weight correlated well with prostate volume on MRI, either by automatic segmentation software or by manual measurement, but not with transrectal US measurement. In our study, automatically measured prostate volume after loading the axial MRIs shows good agreement with manually measured volume from US.…”
Section: Discussionmentioning
confidence: 99%
“…For the risk stratification of cancer, PSA density or PSA divided by prostate volume is a reliable biomarker. In a recent article, Massanova et al [20] reported that the actual surgical specimen weight correlated well with prostate volume on MRI, either by automatic segmentation software or by manual measurement, but not with transrectal US measurement. In our study, automatically measured prostate volume after loading the axial MRIs shows good agreement with manually measured volume from US.…”
Section: Discussionmentioning
confidence: 99%
“…So, our study showed consistent results with the above study. In addition, there is a study that suggests the prostate volume obtained by MRI, either with the ellipsoid or bullet formula, proved to be almost accurate and time- and cost-effective [ 30 ]. Prostate volume was calculated based on TRUS in the above two studies, and more accurate analysis might have been possible if the prostate volume was obtained using MRI.…”
Section: Discussionmentioning
confidence: 99%
“…The total prostate volume (PV) was calculated from the recorded specimen dimensions (length, width, and height) using the ellipsoid formula PV = height × width × length × π/6. For more accurate calculation of prostate volume, the whole mount prostate specimens for both groups were separated from the seminal vesicles and periprostatic fat [ 10 , 11 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%